Microbiology and energy assessment of cultivation of sod-podzolic sand soil under the action of peat and loam - Gaevskii, Eugene E.; Kulikov, Yaroslav K. (Journal of the Belarusian State University. Ecology, 2020)
The paper presents the results of the study on the microflora of sod-podzolic sandy soil in the process of cultivation under the influence of peat and loam. Solving the problem of the effective use of sod-podzolic sandy soils and increasing their fertility is an important task of agricultural soil science and agroecology. The cultivation of sod-podzolic sandy soil under the action of peat and loam soil increases the content of organic matter from 1.4 to 4.1 % and optimizes the structural organization of the microbial complex, which is reflected in an increase in the species diversity of the bacterial flora from 19.4 to 30.6 %. Moreover, in the conditions of cultivated sandy soil, qualitatively new microbial cenoses are formed the species composition of which differs by more than 50 % from the bacterial complexes of uncultivated soil.
Keywords: sandy soil; cultivation; microbial communities; species composition; energy efficiency; productivity